Complexo luminescente de Ru(II)-Perileno: avaliação da citotoxicidade e da fotocitotoxicidade em células de melanoma murino B16F10 in vitro e in vivo - Campos, Isabele Aparecida Soares de (Universidade Federal de São Carlos, 2017)
Cutaneous melanoma is one of the most feared cancers worldwide due to resistance to treatments and the high capacity to develop metastases. Photodynamic therapy (PDT), a minimally invasive therapeutic modality, is a promising treatment strategy for malignant and non-malignant lesions. Ru (II) polypyridine complexes are interesting photosensitizers for PDT due to their unique spectroscopic and anticancer properties. This study reports the extension and implications of medium on the aggregation process of the [Ru(phen)2(pPDIp)]2+ complex (RupPDIp), where phen = 1,10-phenanthroline and pPDIp = perylene pendant group functionalized with one of the coordinated phenanthroline ligands) and its consequences on photochemical and photophysics properties. Excitation with visible light leads, initially, to emission of both chromophores inside the same molecule: 3*MLCT (Ru,dπ→phen,π*) and 1*ILCT (pPDIp,π→π*); however, the medium induces increased π-π intermolecular interactions that lead to generation of the pPDIp moiety in the radical anion forms pPDIp•- in DMSO, pPDIp•- and pPDIp2- in cellular culture medium RPMI, and 3*pPDIp in buffer solution (pH 7.4), and starch films. Thus, it is demonstrated that variation of solvent alone can be used to tune the energy of the excited state in a manner that leads to systematic variations in the photoreactivity and emissive properties of the complex. The complex also exhibited an interesting profile for biological activity with the activation of singlet oxygen (1O2) in buffer solution (pH 7.4) under irradiation by different light systems. The potential of the complex for application in photodynamic therapy to B16F10 murine melanoma cells in vitro was also evaluated. No cytotoxic effects were observed at concentrations of the complex of less than 10 μmolL-1 in the dark. However, the complex showed a significant photocytotoxic effect presenting IC50 values of 0.5 μmolL-1 when treated with 420 nm light at a dose of 0.58 J.cm-2 and 1.2 μmolL-1 when treated with 518 nm LED light at a dose of 0.11 J.cm-2. These results demonstrate that RupPDIp is a promising candidate for the application of photosensitization in photodynamic therapy. In order to facilitate the application and control of RupPDIp as an antitumor agent, the complex was immobilized on a cassava starch-based polymer film. Spectroscopic assays demonstrated that the complex adhered to the π-π aggregate form when immobilized on the film, maintaining its luminescent properties and activation of 1O2 with exposure to light. In vitro and in vivo biological assays did not show significant results in antitumor activity due to the 1O2 limited action radius, demonstrating that the film is not the most suitable drug delivery medium.
Luminescent ru(ii)-perylene complex: evaluation of cytotoxicity and photocytotoxicity in vitro and in vivo in b16f10 murine melanoma cells
Keywords: Melanoma; Complexos de Rutênio(II); Fotoquímica; Fotossensibilizador; Terapia fotodinâmica; Oxigênio singleto; Cutaneous melanoma; Photodynamic therapy; CIENCIAS EXATAS E DA TERRA::QUIMICA